BONES WITH BIOCERAMICS - Wijianto Wijianto (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2007)
This paper discuss about ceramics in application as bone implant. Bioceramics for instance Hydroxyapatite, usually is abbreviated with HA or HAp, is a mineral that is very good physical properties as bone replacement in human body. To produce Hydroxyapatite, coating process is used which have good potential as they can exploit the biocompatible and bone bonding properties of the ceramic. There are many advantages and disadvantages of bioceramics as bone implant. Advantages of hydroxyapatite as bone implant are rapidly integrated into the human body, and is most interesting property that will bond to bone forming indistinguishable unions. On contrary, disadvantages of hydroxyapatite as bone implant are poor mechanical properties (in particular fatigue properties) mean that hydroxyapatite cannot be used in bulk form for load bearing applications such as orthopaedics and poor adhesion between the calcium phosphate coating and the material implant will occur.